A conceptual framework on strengthening physical resilience components for community in flood-prone areas in Kelantan / Ezzat Fahmi Ahmad - Ahmad, Ezzat Fahmi (2022)
Natural disasters have become more frequent and intense around the world. Malaysia has no exception where the flood is the most devastating natural disaster experienced by this country. Flood has caused massive damage and disruption to physical resilience components such as energy and water supply, transportation and telecommunication systems, and critical facilities like hospitals and shelters, particularly in Kelantan. Thus there is an extreme need to have physical resilience components to resist, absorb, accommodate and recover from the effect of floods in a timely and efficient manner as addressing global sustainability measures defined by the United Nations, including Goal 9 regarding resilient infrastructure, Goal 11 regarding resilient cities and Priorities 3 Sendai Framework for Disaster Risk Reduction 2015 – 2030 which to invest in disaster risk reduction for resilience and strengthen critical infrastructure. Therefore, this study aims to develop a framework on strengthening physical resilience components for the community in flood-prone areas in Kelantan. To achieve the aim of this study, this study emphasizes the three objectives: (1) To determine the most important resilience criteria to strengthen physical resilience components for the community in flood-prone areas in Kelantan; (2) To identify the most important physical resilience components for the community in flood-prone areas in Kelantan; (3) To develop a framework for strengthening physical resilience components for the community in flood-prone areas in Kelantan.